ANALISIS STRATEGI PROPOSISI NILAI PADA PRODUK LOKAL: STUDI KASUS PRODUK SEPATU WANITA BERBASIS PENGRAJIN LOKAL DAERAH - Krisna, Krisnayanti Aditasari; Mutiarasari, N. Azizia Gia; Musa, Hussein Gibreel (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Local brands face significant challenges in building a strong value proposition amid intense competition with mass-produced products and well-established brands. Many local brands have not yet been able to clearly articulate a unique and relevant brand value for consumers. Currently, the development of locally based fashion industries is accelerating, particularly in women’s footwear products. The widespread promotion of the Local Pride trend across various media has also contributed to increasing public awareness of local brands. This study aims to analyze how a local women’s footwear brand builds its value proposition through artisan-based branding strategies. The research adopts a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation involving the business founder and operational activities. The findings reveal that the value proposition is constructed through a combination of product functionality, emotional branding approaches, and the empowerment of local artisans. The integration of these elements creates meaningful brand differentiation and enhances consumer trust in product selection. This study provides practical contributions to the development of branding strategies for local fashion brands and enriches the literature on value-based marketing within the creative industry.